The role of offensive metaphors in Chinese diplomatic discourse. (October 2020) - Liu, Wenyu; Wang, Yingjie
Abstract: This paper examines metaphors that are intended to express an offensive meaning in Chinese diplomatic discourse, and the role that these metaphors play in the discursive construction of the ascribed identities of various countries. It pays particular attention to the period between 1954 and 1966 and, in so doing, fills an important knowledge gap as historical Chinese political metaphors have been somewhat neglected in the field. This study of Chinese metaphors reveals that the source domains PERSONIFICATION, PERSON, ANIMAL and PERFORMANCE were most frequently used to evoke offence in the Chinese political arena. The way in which these offensive metaphors were deployed was dependent on the political situation at that time: for instance, the U.S. was constructed as a 'tough' political 'exploiter' who was supported by a 'band' of minor allies, India as an 'unreasonable' representative of the Americans while asserting non-alignment in diplomacy, and the Soviet Union as a 'cold-blooded' former friend of China. This historical study is significant for two main reasons. First, it presents the complex socio-political contexts that existed during 1954–1966 when China was undergoing diplomatic development and their influence on the pragmatic use of metaphors for delivering offence. Although some of the metaphors might appear to be outdated when compared with present-day Chinese political language, this change reflects developments in the global political situation and Chinese diplomatic language over the last number of decades. Second, the study highlights the cultural characteristics of Chinese metaphors and demonstrates their use in political discourse for persuading the Chinese public.